Perforated concave rectangular winglet pair vortex generators enhance the heat transfer of air flowing through heated tubes inside a channel - Oktarina Heriyani; Mohammad Djaeni; Syaiful; Aldila Kurnia Putri (Results in Engineering, 2022)
A significant increase in the rate heat transfer in a heat exchanger system is made possible by increasing the convection heat-transfer coefficient using a passive method. The addition of vortex generators (VGs) to the fins and tubes of a heat exchanger is currently the most effective passive method. However, the increase in heat was accompanied by an increase in pressure drop. Therefore, in this study, we installed perforated concave rectangular winglet pair vortex generators (PCRWP VGs) on plates in rectangular ducts to increase the heat transfer through the six heated tubes to the air stream by lowering the enhancement in the pressure drop. We attempted to determine the best cost-benefit ratio (CBR) with a fluid flow velocity difference of 0.4–2 m/s at intervals of 0.2 m/s (Reynolds number (Re) of 2143 to 11,763) in the channel. The PCRWP VGs were composed of in-line and staggered configurations. The results showed a lower CBR (3.56) for the in-line configuration than for the staggered configuration. Moreover, the lowest CBR was accompanied by an increase in thermal performance (TEF) of 1.29.